Silicon nitride composite material, and probe guide component

A silicon nitride composite material with controlled Si3N4 and Mg2SiO4 composition and microstructure addresses the need for high-strength, thermally stable probe guide components, enhancing mechanical properties and thermal expansion matching silicon wafers.

JP2025005873APending Publication Date: 2025-01-17KROSAKI HARIMA CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023106282
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Conventional probe guide components made of free-cutting ceramics lack high strength and rigidity, and there is a need for materials with thermal expansion coefficients similar to silicon wafers to withstand probe loads and temperature variations.

Method used

A silicon nitride composite material comprising Si3N4 and Mg2SiO4 with controlled microstructure and specific peak intensity ratios, sintered at lower temperatures to achieve high strength and thermal expansion matching silicon wafers.

Benefits of technology

The composite material provides stable thermal expansion, high strength, and rigidity, suitable for probe guide components, with improved mechanical properties and thermal stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025005873000002
    Figure 2025005873000002
  • Figure 2025005873000003
    Figure 2025005873000003
  • Figure 2025005873000004
    Figure 2025005873000004
Patent Text Reader

Abstract

To provide a silicon nitride composite material stably capable of having a heat expansion coefficient and high strength equivalent to those of a silicon wafer and high rigidity as well, and a probe guide component.SOLUTION: The silicon nitride composite material contains 55 mass% or more and 85 mass% or less of Si3N4 and 15 mass% or more and 45 mass% or less of Mg2SiO4, wherein a peak intensity ratio: Iβ / (Iα+Iβ) is 0.2 or less and relative density is 95% or more, provided that Iα represents a (210) plane peak intensity of α-Si3N4 and Iβ represents a (210) plane peak intensity of β-Si3N4, according to powder X ray diffraction. The probe guide component includes a plate-like body using the silicon nitride composite material and a plurality of through-holes and / or slits for the probe to be inserted therethrough into the body.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to silicon nitride composite materials and probe guide components. [Background technology]

[0002] A large number of IC chips and LSI chips are fabricated on a single silicon wafer, which are then cut into individual chips for use. A probe card is used to check whether each chip is defective before it is cut into individual chips. The structure of a probe card, as disclosed in Patent Document 1, for example, includes a substrate to which one end of a probe is attached, and a guide plate (probe guide component) that guides the probe so that it can slide freely. The tip of the probe is accurately brought into contact with a pad (electrode) of an IC chip or an LSI chip formed on a silicon wafer by inserting the probe into a guide hole in the guide plate. Then, in this contact state, an electrical signal is applied, and the electrical signal output from the chip is analyzed to determine whether the chip is defective. This check is often performed, for example, at room temperature or in a high-temperature environment (for example, 80 to 150°C). Therefore, this type of probe card guide plate (probe guide component) is required to have a thermal expansion coefficient similar to that of a silicon wafer in a temperature range from room temperature to about 200°C.

[0003] Conventional probe guide parts are mainly made of machinable ceramics as disclosed in Patent Document 2, for example, and therefore do not have high strength. On the other hand, probe guide parts are also required to have mechanical strength (bending strength) sufficient to withstand the probe load, and in recent years, there has been an increasing demand for higher strength. Under these circumstances, the present inventors have proposed, in Patent Document 3, a method for producing a high-strength ceramic, Si 3 N 4 2. High expansion ceramics ZrO 2 It was disclosed that combining the above is effective. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2003-215163 A [Patent Document 2] JP 2005-226031 A [Patent Document 3] Patent No. 7068539 Summary of the Invention [Problem to be solved by the invention]

[0005] The present inventors decided to explore new silicon nitride composite materials with the aim of improving the silicon nitride composite material of Patent Document 3, particularly increasing its rigidity. As probe guide parts become larger, not only high strength but also high rigidity is required.

[0006] Therefore, the problem that the present invention aims to solve is to provide a silicon nitride composite material and a probe guide component that can stably possess a thermal expansion coefficient and high strength equivalent to those of a silicon wafer, as well as high rigidity. [Means for solving the problem]

[0007] In order to solve the above problems, the inventors conducted tests and research, and as a result, developed a high-strength Si 3 N 4 In addition, ZrO 2 Mg has a higher thermal expansion coefficient than 2 SiO 4 Furthermore, the inventors have found that combining Si 3 N 4 to Mg 2 SiO 4 In order to stably provide the same thermal expansion coefficient and high strength as silicon wafers and also to enable high rigidity in silicon nitride composite materials, Si 3 N 4 , Mg 2 SiO 4We found that it is important to control not only the content of each component but also the microstructure of silicon nitride composite materials. In controlling the microstructure of silicon nitride composite materials, we used powder X-ray diffraction to determine the αSi 3 N 4 The (210) peak intensity of I α , βSi 3 N 4 The (210) peak intensity of I β Peak intensity ratio when: I β / (I α +I β It has been found that it is important to keep the value of the stoichiometric ratio (S) within a specified range.

[0008] That is, according to one aspect of the present invention, there is provided the following silicon nitride composite material. S 3 N 4 55% by mass or more and 85% by mass or less, Mg 2 SiO 4 Contains 15% by mass or more and 45% by mass or less, αSi by powder X-ray diffraction 3 N 4 The (210) peak intensity of I α , βSi 3 N 4 The (210) peak intensity of I β When the peak intensity ratio is I β / (I α +I β ) is 0.20 or less, A silicon nitride composite material having a relative density of 95% or more.

[0009] According to another aspect of the present invention, there is provided a probe guide component for guiding a probe of a probe card, the probe guide component comprising a plate-shaped main body portion made of the silicon nitride composite material of the present invention, and a plurality of through holes and / or slits in the main body portion for inserting the probes therethrough. Effect of the Invention

[0010] According to the present invention, it is possible to provide a silicon nitride composite material and a probe guide component which can stably possess a thermal expansion coefficient and high strength equivalent to those of a silicon wafer, as well as high rigidity. [Brief description of the drawings]

[0011] [Figure 1] 1 shows powder X-ray diffraction intensity data for a silicon nitride composite material according to one embodiment of the present invention (Example 4 in Table 1). [Diagram 2] 1 is a cross-sectional SEM photograph of a silicon nitride composite material according to one embodiment of the present invention (Example 4 in Table 1). [Diagram 3] 1 is a SEM photograph of a cross section of a silicon nitride composite material according to a comparative example of the present invention (Comparative Example 4 in Table 1). [Figure 4] 1 is a photograph showing the appearance of a silicon nitride composite material according to a comparative example of the present invention (Comparative Example 6 in Table 1). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The silicon nitride composite material of the present invention is a high-strength Si 3 N 4 In addition, ZrO 2 Mg has a higher thermal expansion coefficient than 2 SiO 4 In this way, Si 3 N 4 to Mg 2 SiO 4 By combining ZrO 2 Compared with the combination of That is, the first advantage is that the density is 3.1 to 3.2 g / cm 3 This is because the Si 3 N 4 Mg to be compounded 2 SiO 4 The theoretical density is 3.1g / cm 3 and ZrO 2 6g / cm 3 This is due to the fact that it is lower than The second advantage is manufacturing stability. 3 N4 The theoretical density is 3.2g / cm 3 This is because the densities of the two materials are roughly the same, making it easy to mix the raw materials uniformly. The third advantage is that it is possible to obtain a high rigidity. 2 SiO 4 When compounding, the amount of addition is ZrO 2 High rigidity Si 3 N 4 Low rigidity Mg 2 SiO 4 or ZrO 2 When Mg is added, the elastic modulus decreases linearly with the amount of added Mg. 2 SiO 4 By combining these, it is possible to obtain high rigidity.

[0013] The silicon nitride composite material of the present invention is Si 3 N 4 55% by mass or more and 85% by mass or less, Mg 2 SiO 4 Contains 15% by mass or more and 45% by mass or less of Si. 3 N 4 If the Si content is less than 55 mass%, it is difficult to obtain high strength and high rigidity. 3 N 4 If the Si content exceeds 85 mass %, it becomes difficult to obtain a thermal expansion coefficient similar to that of a silicon wafer. 3 N 4 The content is preferably 64% by mass or more and 82% by mass or less. In addition, Mg 2 SiO 4 If the content of Mg is less than 15 mass %, a high thermal expansion coefficient cannot be obtained, and it becomes difficult to obtain a thermal expansion coefficient equivalent to that of a silicon wafer. 2 SiO 4 If the content of Mg exceeds 45 mass %, the thermal expansion coefficient becomes too high, making it difficult to obtain a thermal expansion coefficient equivalent to that of a silicon wafer. 2 SiO 4 The content is preferably 18% by mass or more and 36% by mass or less. The relative density must be 95% or more. If it is less than 95%, pores will remain in the internal structure and the material will not have high strength.

[0014] The silicon nitride composite material of the present invention is αSi 3 N 4 The (210) peak intensity of Iα, βSi 3 N 4 When the (210) plane peak intensity is Iβ, one of the characteristics is that the peak intensity ratio: Iβ / (Iα+Iβ) (hereinafter simply referred to as "peak intensity ratio") is 0.20 or less. If the peak intensity ratio exceeds 0.2, the mechanical strength decreases. The reason for this will be explained below.

[0015] The thermal expansion properties of silicon nitride composite materials can be controlled by Si 3 N 4 , Mg 2 SiO 4 This is possible by controlling not only the content of each component but also the microstructure. The inherent high strength of silicon nitride also depends on the microstructure. The inventors have found that the peak intensity ratio in powder X-ray diffraction of silicon nitride is important for accurate control.

[0016] In the case of Patent Document 3, silicon nitride is basically used as the starting material for silicon nitride composite materials. 3 N 4 The raw material, zirconia, is Y 2 O 3 ZrO stabilized with 2 The raw materials are mixed and sintered in the same way as in normal ceramic manufacturing. During the sintering process, the ceramic particles grow. This is the same for silicon nitride and zirconia. Silicon nitride has an αSi crystal structure. 3 N 4 From βSi 3 N 4 The βSi 3 N 4 This results in needle-like crystals with a high aspect ratio. This is the mechanism by which strength is increased in the case of Patent Document 3.

[0017] However, Mg 2 SiO 4 In the present invention, the needle-shaped βSi with a high aspect ratio is 3 N 4 It is not possible to manufacture at sintering temperatures where a large amount of crystals are formed. 2 SiO 4 The constituent oxide of MgO-SiO 2 The eutectic temperature is 1550°C, and in this system, needle-like βSi with high aspect ratio is formed. 3 N 4 This is because at sintering temperatures at which a large amount of crystals are formed (for example, 1600°C or higher), an excessive liquid phase appears and a uniform sintered body cannot be obtained. Therefore, the present inventors have realized high strength using an approach completely different from that of Patent Document 3.

[0018] That is, in the present invention, βSi 3 N 4 The present invention provides a silicon nitride composite material having high strength while minimizing the formation of αSi 3 N 4 In the gaps between the close-packed crystal grains, Mg 2 SiO 4 High strength was achieved by creating a structure in which spherical particles are filled with αSi. More specifically, the packing rate when spherical particles are closely packed is calculated to be 67% in the case of a body-centered cubic lattice structure, and the remaining 33% is gaps (space). Therefore, in the present invention, the close-packed αSi 3 N 4 The spaces between the crystal grains are almost completely filled with Mg 2 SiO 4 By filling the gap with this, it was possible to achieve high strength as a dense ceramic. As described above, in the present invention, αSi 3 N 4 The crystal particles (silicon nitride particles) do not sinter with each other, and Mg 2 SiO 4 By making forsterite function as a binder between silicon nitride particles, a dense, high-strength silicon nitride composite material (silicon nitride-forsterite composite material) is provided.

[0019] As described above, the silicon nitride composite material of the present invention is basically made of silicon nitride, αSi, as a starting material. 3 N 4 The raw material, forsterite, is a pre-synthesized Mg 2 SiO 4 It is preferable to use a high-purity raw material produced by vapor phase synthesis for silicon nitride, but other manufacturing methods are also acceptable. In this case, Fe 2 O 3 Impurities such as magnesium, alkali, and alkaline earth metals may be included, but as long as the total amount of these impurities is less than 1 mass%, there is no problem. 2 SiO 4 As for the raw material, a high-purity raw material is preferable, but the raw material produced industrially contains abraded Al from the mixing and grinding media. 2 O 3 , ZrO 2 In some cases, impurities such as fluorine, fluorine, and arsenic may be mixed in. In that case, there is no problem as long as the total amount of impurities is 5 mass% or less. The content of each of the above-mentioned components in the silicon nitride composite material of the present invention can basically be determined by ICP atomic emission spectrometry and N and O analysis.

[0020] The silicon nitride composite material of the present invention can be obtained by mixing the starting materials and sintering the molded body, as in the case of ordinary ceramic production. In order to achieve a relative density of 95% or more, however, it is preferable to carry out a hot press treatment or a HIP treatment after pressureless sintering. As described above, one of the features of the silicon nitride composite material of the present invention is that the peak intensity ratio is 0.20 or less, and this peak intensity ratio can be controlled by the sintering temperature. Specifically, as shown in the examples described later, the peak intensity ratio can be made 0.20 or less by setting the sintering temperature to 1500°C or less. In addition, the sintering temperature can be adjusted by controlling the sintering temperature of the MgO-SiO 2 By setting the temperature at 1500°C or lower, which is lower than the eutectic temperature of the system (1550°C), it is possible to prevent the appearance of an excess liquid phase during sintering. The lower limit of the sintering temperature is not particularly limited, but in the examples described below, the lower limit is 1400°C.

[0021] By controlling the content and peak intensity ratio of each component to fall within a predetermined range as described above, it is possible to obtain a silicon nitride composite material that stably exhibits a thermal expansion coefficient and high strength equivalent to that of a silicon wafer. Specifically, as shown in the examples described later, the thermal expansion coefficient from room temperature to 200°C is 3×10 -6 / ℃ or more 6×10 -6 / °C or less, and a bending strength of 400 MPa or more can be stably obtained.

[0022] The silicon nitride composite material of the present invention is suitable for use as a main body of a probe guide component that guides probes in a probe card. That is, the probe guide component of the present invention comprises a plate-shaped main body using the silicon nitride composite material of the present invention, and a plurality of through holes and / or slits for inserting the probes therethrough.

[0023] The shapes of probe card guide parts generally range from 25mm square to 300mm diameter, but the larger the shape and the more probes there are, the greater the bending moment acting on the surface. In order for guide parts to reduce deflection due to the bending moment and accurately guide the probes, the elastic modulus of the material is also an important factor. 3 N 4 (Silicon nitride) originally has an elastic modulus of 300 GPa or more, but ZrO 2 (Zirconia) and Mg 2 SiO 4 The addition of forsterite (zirconia) reduces the elastic modulus. In this respect, the forsterite added in the present invention has a larger thermal expansion than zirconia, so that a small amount of forsterite can be added to obtain the desired thermal expansion coefficient. Therefore, in the present invention, it is possible to obtain a material having an elastic modulus of 300 GPa or more, as shown in the examples described later.

[0024] The silicon nitride composite material of the present invention can also be used for inspection sockets such as package inspection sockets, which are applications requiring performance similar to that of a probe guide part that guides a probe in a probe card. EXAMPLES

[0025] In order to confirm the effect of the present invention, the compounding ratio of α-Si was changed. 3 N 4 Powder and Mg 2 SiO 4 The powder was mixed with water, a dispersant, a molding aid, and ceramic balls in a ball mill, and the resulting slurry was spray-dried in a spray dryer to form granules. The granules were press-molded into a molded body of 40 mm square x 30 mm t at a pressure of 140 MPa, and the molding aids and other additives were degreased. The degreased body was then set in a graphite die and hot-press sintered at 1400°C to 1600°C for 2 hours while applying a pressure of 30 MPa in a nitrogen atmosphere, to obtain a test material of 40 mm length x 40 mm width x 15 mm thickness. Test pieces were then taken from the obtained test material, and the relative density, peak strength ratio, thermal expansion coefficient, bending strength, and elastic modulus were evaluated, and an overall evaluation was performed based on the results of these evaluations. The α-Si 3 N 4 Powder and Mg 2 SiO 4 The powder used was of high purity and substantially free of impurities. Table 1 shows the compositions and evaluation results of silicon nitride composite materials according to examples of the present invention and comparative examples.

[0026] [Table 1]

[0027] The evaluations of relative density, peak intensity ratio, thermal expansion coefficient, bending strength and elastic modulus, as well as the overall evaluation, were carried out as follows. <Relative density> The bulk specific gravity of each test piece was measured by the Archimedes method. The test pieces were then finely ground in a mortar and pestle made of WC, and the true specific gravity was measured by the pycnometer method. The relative density was calculated by dividing the bulk specific gravity by the true specific gravity.

[0028] <Peak intensity ratio> As an example of powder X-ray diffraction, the powder X-ray diffraction intensity data of Example 4 is shown in FIG. 1. Based on such powder X-ray diffraction intensity data, αSi 3 N 4 (210) peak intensity: I α , and βSi 3 N 4 (210) peak intensity: I β The peak intensity ratio is: I β / (I α +I β In the powder X-ray diffraction intensity data of Example 4 (FIG. 1), βSi 3 N 4 The (210) plane peak intensity is 0.

[0029] <Thermal expansion coefficient> The thermal expansion coefficient of each test piece from room temperature to 200°C was determined in accordance with JIS R1618. -6 The evaluation of the thermal conductivity (TC) was as follows: ⊚ (excellent) if it was 3.5 or more and 5 or less, ◯ (good) if it was 3 or more and less than 3.5 or more and less than 6, × (low) (poor) if it was less than 3, and × (high) (poor) if it was more than 6.

[0030] <Bending strength> The four-point bending strength of each test piece was determined in accordance with JIS R 1601. The bending strength (unit: MPa) was evaluated as follows: ⊚ (excellent) if 600 or more, ◯ (good) if 400 or more and less than 600, and × (poor) if less than 400.

[0031] <Elasticity modulus> The elastic modulus of each test piece was determined in accordance with JIS R 1602. The elastic modulus (unit: GPa) was evaluated as follows: ⊚ (excellent) when it was 300 or more, ◯ (good) when it was 250 or more and less than 300, and × (poor) when it was less than 250.

[0032] <Overall rating> A sample was rated as excellent if both the thermal expansion coefficient and bending strength were rated as excellent and the elastic modulus was rated as good (◎), a sample was rated as good if at least one of the thermal expansion coefficient and bending strength was rated as good and there were no poor ratings for the thermal expansion coefficient, bending strength, and elastic modulus, and a sample was rated as poor if at least one of the thermal expansion coefficient, bending strength, and elastic modulus was rated as poor.

[0033] In Table 1, the compositions (contents of each component) and peak intensity ratios of Examples 1 to 6 are all within the ranges of the present invention, and the overall evaluations are ◎ (excellent) or ◯ (good), indicating that good results were obtained. Among them, Examples 2 to 4, in which the compositions and peak intensity ratios are all within the preferred ranges, were overall evaluated as ◎ (excellent), indicating that particularly good results were obtained. In addition, Fig. 2 shows a cross-sectional SEM photograph of the silicon nitride composite material according to Example 4. 3 N 4 Almost completely between Mg 2 SiO 4 It appears to be filled with water.

[0034] In Table 1, Comparative Example 1 is Mg 2 SiO 4 This is an example in which the content of Mg was too low. The sinterability was poor and the relative density was below the specified value (95%) of the present invention. Therefore, the bending strength was evaluated as "× (bad)". 2 SiO 4 The thermal expansion coefficient was rated as "x (low)" because the content of 100% was relatively low. The elastic modulus was also affected by the density, so it was rated as "x (poor)." Comparative Examples 2 and 3 are Mg 2 SiO 4 The thermal expansion coefficient was evaluated as "x (high)." In Comparative Examples 2 and 3, the peak intensity ratio was not evaluated. Comparative Examples 4 and 5 are examples in which the peak intensity ratio is too high. The bending strength was evaluated as × (bad). FIG. 3 shows a cross-sectional SEM photograph of the silicon nitride composite material according to Comparative Example 5. βSi 3 N 4The formation of these compounds disrupts the fine crystal grain structure, causing small gaps to appear and reducing strength. Comparative Example 6 is MgO-SiO 2 This is an example where the material was sintered at 1600°C, which is higher than the eutectic temperature of the system (1550°C). A liquid phase was generated during sintering, resulting in a non-uniform sintered body (see Figure 4). The peak intensity ratio was also high at 0.5. Note that, since Comparative Example 6 resulted in a non-uniform sintered body, evaluation was not performed for anything other than the peak intensity ratio.

[0035] As described above, according to the present invention, it is possible to obtain a silicon nitride composite material that stably has a thermal expansion coefficient and high strength equivalent to those of a silicon wafer. In addition, as shown in Example 2, it is also possible to obtain a silicon nitride composite material that has a high elasticity of 300 GPa or more, specifically 304 GPa. On the other hand, when the present inventors evaluated the elastic modulus of the silicon nitride composite material of Patent Document 3, the maximum value was 283 GPa. In other words, according to the present invention, it is possible to obtain a silicon nitride composite material that stably has a thermal expansion coefficient and high strength equivalent to those of a silicon wafer, and also has high rigidity.

Claims

1. S 3 N 4 55% by mass or more and 85% by mass or less, Mg 2 SiO 4 Contains 15% by mass or more and 45% by mass or less, αSi by powder X-ray diffraction 3 N 4 The (210) plane peak intensity of I α , βSi 3 N 4 The (210) plane peak intensity of I β When the peak intensity ratio is I β / (I α +I β ) is 0.20 or less, A silicon nitride composite material having a relative density of 95% or more.

2. A probe guide component for guiding a probe of a probe card, A plate-shaped main body using the silicon nitride composite material according to claim 1; A probe guide component comprising a main body portion having a plurality of through holes and / or slits through which the probes are inserted.

Citation Information

Patent Citations

  • Probe card

    JP2003215163A

  • Machine processing material and method for producing the same

    JP2005226031A

  • Silicon nitride composite material and probe guide parts

    JP7068539B1